Dreams of Falling - White, Karen ([Place of publication not identified]: Penguin Publishing Group, 2018)
One of PureWow's "Best Beach Reads of Summer 2018" New York Times bestselling author Karen White crafts evocative relationships in this contemporary women's fiction novel, set in the Lowcountry of South Carolina, about lifelong friends who share a devastating secret. On the banks of the North Santee River stands a moss-draped oak that was once entrusted with the dreams of three young girls. Into the tree's trunk, they placed their greatest hopes, written on ribbons, for safekeeping--including the most important one: Friends forever, come what may. But life can waylay the best of intentions.... Nine years ago, a humiliated Larkin ...